2003
DOI: 10.1038/sj.leu.2402978
|View full text |Cite
|
Sign up to set email alerts
|

A cholesterol-dependent CD20 epitope detected by the FMC7 antibody

Abstract: Accurate diagnosis of lymphoid malignancies is essential for appropriate therapeutic intervention. In conjunction with other diagnostic determinants, immunophenotypic analysis of differentially expressed cell surface markers, such as CD5, CD20, CD23 and FMC7, is useful in the subclassification of lymphomas and leukemias arising from the B-cell lineage. Recent evidence suggesting that CD20 predicts FMC7 expression has prompted reappraisal of the utility of monitoring both markers. Here, we report that the FMC7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…Thus, the resistance of CD20 to CHAPS may indicate that its constitutive raft localization is mediated by interactions with lipids rather than proteins. Consistent with this notion, the conformation of CD20 was recently shown to be sensitive to the level of membrane cholesterol, suggesting a potentially direct CD20-cholesterol interaction (27).…”
Section: Discussionsupporting
confidence: 61%
“…Thus, the resistance of CD20 to CHAPS may indicate that its constitutive raft localization is mediated by interactions with lipids rather than proteins. Consistent with this notion, the conformation of CD20 was recently shown to be sensitive to the level of membrane cholesterol, suggesting a potentially direct CD20-cholesterol interaction (27).…”
Section: Discussionsupporting
confidence: 61%
“…Studies suggest that anti-FMC7 antibody binds to a conformationally determined epitope on the CD20 antigen (17,18). It is interesting to note that the cluster with decreased CD20 expression (i.e., the high CD38 typical BCLL cluster) also had concurrently decreased FMC7 expression.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Interestingly, Polyak et al found that FMC7 may be an indicator of membrane cholesterol content as cholesterol depletion markedly diminishes the expression of FMC7. 17,35 Thus, samples with discordant CD20 may represent a form of DLBCL that has an altered membrane cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This was also true for FMC7, an epitope of CD20 (data not shown). 16,17 Interestingly, one sample showed at least 3 populations of CD19 ϩ cells displaying different intensities of FMC7, suggesting that clonal populations with different CD20 expression can exist within the same tumor ( Figure S1, available on the Blood website; see the Supplemental Materials link at the top of the online article). All but one sample with "dim" CD20 expression also had "dim" expression for FMC7.…”
Section: Cd20 Expression By Fcm Is Heterogeneousmentioning
confidence: 99%